Computational-experimental investigation of milling porous aluminium. Issue 1 (2017) - Michailidis, N.; Kombogiannis, S.; Charalampous, P.; Maliaris, G.; Stergioudi, F.
Abstract: Porous materials are increasingly incorporated in light-weight structures and although they are near-net-shape fabricated, a finishing step is required to achieve the desired tolerances. Herein, a computational-experimental framework is proposed to investigate milling of porous aluminium. A FEM model was built, for the first time recorded in the literature, to simulate the milling process of the 3D closed-cell porous geometry, reconstructed by a Voronoi-based CAD algorithm. The chip evolution, traced by the developed FEM model, reveals interesting deformation mechanisms, while the chip fragmentations lead to multiple force fluctuations in a single cut, offering a good agreement with the measured forces.